Mønster, variasjon og improvisasjon i eit filma dansemateriale: Springarvariantar frå Sørfjorden i Hardanger - Mæland, Siri; Rosvold, Magni; Velure , Magne (Puls – musik- och dansetnologisk tidskrift, 2025)
Variations of the regional dance springar from Sørfjorden in Hardanger. Patterns and variations in a film archive material. In our project, we have studied the relationship between human creativity and human structuring activity through a close analysis of a particular dance type, the springar from Sørfjorden in the Hardanger region of Norway. Our results may serve as hypotheses for testing how movement material has been structured and varied over time in other traditional areas or dance types, both in Norway and abroad. The findings may also serve as hypotheses for testing different models for teaching and transmitting traditional dance, and, in particular, as a tool for discussing and choosing safeguarding strategies. On the west coast of Norway, a particular dance form, the springar from Sørfjorden in Hardanger, located in the Vestland region, has been recognised since the 1930s. Fieldwork in this fjord, particularly from 1967 and 1982, and new fieldwork from 2005 and 2020–2022, has resulted in a film archive with over 40 unique realisations of springar dancing. The springar is a regional dance that historically predates 19th century European couple dances. The springar has been transmitted and revived in different periods, and among different generations and communities in the fjord. Our thorough analysis of structure, motifs, rhythm, and steps in the filmed material reveals different patterns of movement, where improvisational elements and interpretations of rhythm, such as the undivided meter, play an important role in the dance, even among ordinary dancing community members. The material offers new insights into how even the most structured «course variants» can display human creativity, and how different interpretations and teaching models may intertwine with each other, as well as with the still-present traditional bearers of the region. Our analysis shows a multi-layered tradition where simple motifs and step patterns are as common as improvisational motif combinations and intricate step patterns – a tradition in which each individual adds their own personal touch, leaving their mark on the tradition.